القيم التنظيمية وتأثيرها في الأداء الاستراتيجي بحث ميداني مقارن بين جامعتي بغداد والنهرين - الملا, عبد الرحمن مصطفى; احمد, ليلى سعيد (Journal of Economics and Administrative Sciences, 2016)
ABSTRACT      The researcher seeks to shed light on the relationship analysis and the impact between organizational values in all its dimensions (Administration Management, Mission, relationship management, environmental management) and strategic performance (financial perspective, customer perspective, the perspective of internal processes, learning and development) in the presidency of Two Universities of Baghdad & Al-Nahrain, it has been formulating three hypotheses for this purpose.      The main research problem has been the following question: Is there a relationship and the impact of between organizational values and strategic performance? and to clarify the relationship between research variables, it has to prepare three main hypotheses, The resolution was adopted as a key tool for data collection and analysis were subjected to the questionnaire validity and reliability tests, which included the sample (64) an individual who occupy the post of president of the university, and his assistant, scientific and administrative, and the heads of scientific and administrative departments, and to analyze the Research data used statistical program SPSS and EXCEL program, and of the most important statistical tools used in the analysis is the (percentage, duplicates, mean, standard deviation, coefficient of variation, correlation coefficient, simple regression analysis, and test Mann Whitney).      The research has come to a group of the most important results and the presence of high-level organizational values deportation strategic and performance of all its variables at Two Universities of Baghdad & Al-Nahrain, Among the most prominent results a correlation relationship moral high degree and with proportional effect between organizational values in strategic performance overall and by sub-variants, and also to a number of conclusions most important that he did not show any significant differences between Two Universities of Baghdad & Al-Nahrain in organizational values and strategic performance